Efficacy of biological control against soil-borne pathogens in Catharanthus roseus - Szendrei, Lilla; Borsos, Dóra Piroska; Petróczy, Marietta; Markó, Gábor; Tóth , Annamária (GEORGIKON FOR AGRICULTURE, 2025)
The cultivation of Madagascar periwinkle (Catharanthus roseus L.) is affected by many pathogens, including soil-borne pathogenic fungi such as Fusarium spp., Phytophthora spp., and Pythium spp. The importance of biological control methods has been increasing due to the ongoing phase-out of chemical pesticides. Biocontrol agents like Bacillus amyloliquefaciens, Trichoderma asperellum, and T. atroviride are increasingly used due to their pathogen suppression capabilities and ability to enhance plant resilience to stress. This study evaluated the in vitro efficacy of T. asperellum against F. oxysporum. Significant inhibition of F. oxysporum growth was observed in dual culture confrontation test. Our results highlighted the potential of T. asperellum as a biocontrol agent for managing F. oxysporum in C. roseus cultivation. The application of these agents can reduce the dominance of chemical pesticides and promote sustainable agriculture practices.